Síntese do polipirrol com surfactantes aniônicos visando aplicações como absorvedores de micro-ondas - Campos, Regiane Aparecida Medeiros (2014)
In this work different samples of polypyrrole (PPy) were synthesized varying the combination of FeCl3 and Fe2(SO4)3 as oxidant agents and sodium dodecylbenzenesulfonate (DBSNa) and dodecylbenzenesulfonic acid (DBSA) as surfactants. Infrared spectroscopy analyses showed no significant differences in the chemical structures of synthesized PPy samples. However, thermogravimetric, electrical conductivity and X-ray diffraction analyses showed that the anionic surfactants favored the preparation of samples which are more thermally stable, conducting and with a more ordered crystallographic structure. Reflectivity measurements of PPy/epoxy resin blends, in the frequency range from 8 to 12 GHz, showed microwave attenuation up to 95% of the incident radiation.